Design and Development of a Student Industry Relations and Placement Web-App Using MERN Stack - Gowtham Rudru; MVBT Santhi (Utilitas Mathematica, 2025)
Architecting and Developing Web Portals have expanded rapidly with the advancement of digital innovation. Software-based solutions are developing at a rate comparable to that of hardware. The Internet and real-time-enabled electronic devices have reinforced the growing importance of performance. Regrettably, due to their widespread use and a long history of traditional technology development and maintenance, some of them do not meet current client activity standards. The MERN stack was developed to address this performance issue. This is an application of the web that allows seekers and posters to meet and look for jobs. This project ends with the building and deployment of a functional and production-ready web store application. The results of the application and possible improvements are also covered. This dissertation can serve as an introduction to the MERN stack for beginners along with those thrilled by the discovery of the technology framework.